Characterisation of HIV-1 subtype C envelope functional determinants of dual infected individuals - Omar, Shatha Sultan Ahmed (Department of Integrative Biomedical Sciences (IBMS), 2019)
Identification of HIV-1 Envelope (Env) fitness determinants could provide functionally constrained, accessible regions that could be included in subunit vaccines to induce broadly neutralising antibodies (bnAb). We hypothesised that Env fitness determinants are common to circulating variants but that the plasticity of Env structure limits identification. Rapid evolution; however, could select for sequence changes within the determinants coincident with alterations in function, making identification easier. Dual infection with two phylogenetically distinct HIV-1 variants under the same selective pressures might result in rapid functional evolution, facilitating identification of Env fitness determinants. It has been shown that the Env plays a significant role in viral adaptation to the host environment, which then increases disease progression. Therefore, this study used dual infections as a model system to characterise Env function, its role in in vivo viral outgrowth of variants and disease progression and to identify fitness determinants for future vaccine design. Single-genome amplification (SGA)-derived env sequences of four dual infected individuals sampled at enrolment (0 months), 3, 6, and 12 months post infection (mpi) were analysed using Highlighter plots, RIP, DNA pairwise distance and Neighbourjoining trees to determine the in vivo evolution of infecting viral populations and their relative frequency over time within each participant. Representative amplicons were cloned at each time point and compared using a pseudovirus (PSV) entry efficiency assay. 2 characterised by Affinofile system, T-20 IC50 and Western blotting to identify whether tropism, Env expression/cleavage, incorporation into viral particles and fusogenicity were most likely responsible for the variation in Env entry efficiency. All variants were R5- and T-tropic and only Env fusion capacity correlated significantly with Env entry efficiency data (p = 0.02, r = 0.59), suggesting that variants infecting dual infected participants evolved towards higher fusion capacity. Changes in Env fusogenicity indicated that gp41 might be a fitness determinant of PSV entry efficiency and analysis of SGA sequences indicated that recombination within gp41 was common to 3/4 participants. Env chimeras were generated where gp41 was swapped between clones that either had the same (CAP84) or different (CAP267) PSV entry efficiency. For both participants, and (CAP137) gp41 was identified as a potential determinant of Env fitness. Moreover, two potential N-glycan sites (PNG) at position N332 and N339, previously reported to be involved in neutralising antibody escape, were also identified. While N332 enhanced Env entry efficiency in one participant, N339 attenuated Env entry efficiency in another, potentially due to the escape mutation carrying a fitness cost. However, neither PNG seemed to affect Env expression/cleavage, incorporation into viral particles and fusogenicity. As Env phenotypic characterisation focussed on PSV assays, we wanted to determine whether viral replication was also similarly affected. Infectious molecular clones (IMCs) were generated from two participants using a recombination yeast assay and replication capacity (RC) in peripheral blood mononuclear cells (PBMCs) was assessed using parallel replication. A significant correlation between RC of viruses in PBMCs and Env entry efficiency in TZM-bl and fusion capacity (p = 0.03, r = 0.7; p = 0.04, r = 0.7, respectively) was determined. IMC RC was also associated with in vivo outgrowth of viral populations at 12 mpi although this relationship did not always coincide with the frequency of individual variants. Changes in the RC of the Env chimeras and mutants was not associated with phenotypic changes, suggesting that Env entry efficiency determinants did not play the same role in IMC RC as it did in PSV entry. Lastly, there was a significant negative association (p = 0.046, r = -0.59) between Env entry efficiency and CD4+ T decline, a marker of disease progression, supporting the previous finding that Env entry efficiency could be the driving agent of disease progression. This was also corroborated by the trend in association between RC of IMCs and faster CD4+ T decline. 3 Our findings suggest that despite different host pressures, viral competition in most dual infected individuals selected for rapid recombination within gp41 that enhanced fusion capacity. Enhanced gp41 fusogenicity of the dominant viral population at 12 mpi increased PSV entry efficiency and replicative fitness enabling viral outgrowth. Therefore, vaccines that target gp41 might prevent HIV infection or at least attenuate viral fitness and slow disease progression. On the other hand, we showed that targeting the PNG at position N339 of gp120 might influence viral fitness and increase viral load and/or decrease CD4 T cell count. This is in keeping with the association between CD4 T cell decline and PSV entry efficiency and IMC RC, suggesting that Env fitness plays a role in HIV pathogenicity.